Trajectory of Perinatal Depressive Symptoms from the Second Trimester to Three Months Postpartum and Its Association with Sleep Quality - Wang C; Hou J; Li A; Kong W (Dove Medical Press, 2023)
Chen Wang,1 Jinqin Hou,2 Anning Li,3 Weimin Kong4 1Department of Perinatal Medicine, Beijing Obstetrics and Gynecology Hospital, Capital Medical University, Beijing Maternal and Child Health Care Hospital, Beijing, People's Republic of China; 2Department of Special Education and Psychology, China National Academy of Educational Sciences, Beijing, People's Republic of China; 3The National Clinical Research Center for Mental Disorders & Beijing Key Laboratory of Mental Disorders, Beijing Anding Hospital, Capital Medical University, Beijing, People's Republic of China; 4Department of Gynecological Oncology, Beijing Obstetrics and Gynecology Hospital, Capital Medical University, Beijing Maternal and Child Health Care Hospital, Beijing, People's Republic of ChinaCorrespondence: Weimin Kong, Department of Gynecological Oncology, Beijing Obstetrics and Gynecology Hospital, Capital Medical University, Beijing Maternal and Child Health Care Hospital, No. 251, Yaojiayuan Road, Chaoyang District, Beijing, People's Republic of China, Tel +8618611942798, Email kwm1967@ccmu.edu.cnPurpose: Few studies have explored the association between sleep quality and depressive symptoms in perinatal women from the second trimester to the postpartum period. This study aims to explore this relationship using a longitudinal design.Patients and Methods: Participants were enrolled at 15 gestational weeks. Demographic information was collected. Perinatal depressive symptoms were measured using the Edinburgh Postnatal Depression Scale (EPDS). Sleep quality was measured employing the Pittsburgh Sleep Quality Index (PSQI) at five timepoints from enrollment to three months postpartum. Overall, 1416 women completed the questionnaires at least thrice. A Latent Growth Curve (LGC) model was performed to identify the relationship between the trajectories of perinatal depressive symptoms and sleep quality.Results: Of the participants, 23.7% screened positive at least once on the EPDS. The perinatal depressive symptoms trajectory, fitted by the LGC model, decreased at early pregnancy and increased from 15 gestational weeks to three months postpartum. The intercept of sleep trajectory positively affected the intercept of perinatal depressive symptoms' trajectory; the slope of sleep trajectory positively affected both the slope and the quadratic coefficient of perinatal depressive symptoms' trajectory.Conclusion: The trajectory of perinatal depressive symptoms increased from 15 gestational weeks to three months postpartum following a quadratic trend. Poor sleep quality was associated with depression symptoms beginning at the onset of pregnancy. Moreover, rapidly declining sleep quality could be a significant risk factor for perinatal depression (PND). These findings call for greater attention to perinatal women who report poor and persistently deteriorating sleep quality. Additional sleep-quality evaluations, depression assessments, and referrals to mental health care providers may benefit these women and support PND prevention, screening, and early diagnosis.Keywords: perinatal depression, sleep quality, trajectory, latent growth curve model